2023
DOI: 10.1002/adfm.202212698
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Top and Buried Surface Optimization for Flexible Perovskite Solar Cells with High Efficiency and Stability

Abstract: Although much progress is made toward enhancing the efficiency of perovskite solar cells (PSCs), their operational reliability, particularly their mechanical stability, which is a crucial factor for flexible PSCs (f‐PCSs), has not attracted sufficient attention. The defects in the perovskite layer, especially on the top and the buried surface of the perovskite layer, can induce perovskite fracture, highly limiting the performance of f‐PSCs. Herein, a novel multifunctional organic salt, metformin hydrochloride,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Perovskite materials have distinct advantages of high absorption coefficients, [3][4][5] tunable bandgaps, [6][7] and longer carrier diffusion lengths. [8][9][10] Due to the strong interest in wearable electronics, flexible PSCs (FP-SCs) have also been vigorously explored due to their flexural properties. [7,[11][12][13] In FPSCs, the buried interface between the perovskite and charge-transporting layers strongly affects the film quality and device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite materials have distinct advantages of high absorption coefficients, [3][4][5] tunable bandgaps, [6][7] and longer carrier diffusion lengths. [8][9][10] Due to the strong interest in wearable electronics, flexible PSCs (FP-SCs) have also been vigorously explored due to their flexural properties. [7,[11][12][13] In FPSCs, the buried interface between the perovskite and charge-transporting layers strongly affects the film quality and device performance.…”
Section: Introductionmentioning
confidence: 99%
“…[25] From SEM results, some pinholes and exposed GBs were noticed in the untreated perovskite film (Figure 3B), which would induce carrier losses at the top surface. [26] In contrast, the perovskite films treated by molecules all exhibited uniform grain boundaries and negligible pinholes, which are essential to improving the carrier collection at these interfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Metal halide perovskites, as representative materials, have gained significant attention in PVs and light-emitting devices, with their conversion efficiencies reaching up to 25%. [116,117] Recently, researchers have demonstrated that metal halide perovskites may be suitable for lithium ion storage, [118] suggesting that they are potential PAMs for dual-functional photoelectrodes to simultaneously absorb and store solar energy. [104] In this sense, Ahmad et al [102] investigated the photoelectrochemical performances of C 6 H 9 C 2 -H 4 NH 3 ) 2 PbI 4 (CHPI) in PA-LIBs (Figure 8d) by designing a hybrid device to generate PA-LIBs, in which the 2D CHPI-rGO-polyvinylidene fluoride (PVDF) is sandwiched between a separator and a collector electrode (Figure 8e).…”
Section: Metal Halide Perovskitesmentioning
confidence: 99%